2018
DOI: 10.1007/s00187-018-00272-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on the internal auditors’ work: experiences of Swedish external auditors

Abstract: The purpose of this study is to explore how external auditors experience their decision to rely on internal auditors' work. This study employs both qualitative and quantitative methods consisting of semi-structured interviews and questionnaires administered to external auditors in Sweden. Semi-structured interviews were conducted with external auditors who are working in Big 4 audit firms in Sweden and have engagements with internal audit functions. A questionnaire was administered to authorized/approved audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In this part, we have clarified studies that discussed the relationship of the internal auditors with other parties. These studies have addressed the interrelation between the internal auditors and members of audit committees (Al-shaer and Zaman, 2018;Alzeban and Sawan, 2015;Davies, 2009;Quick and Henrizi, 2019;Zaman and Sarens, 2013) and the internal auditors and external auditors (Abbott et al, 2012;Argento et al, 2018;Morais and Franco 2019). It has been found that IA helps in saving audit costs in addition to enhancing and improving audit efficiency (Abbott et al, 2012).…”
Section: Internal Auditors and Other Partiesmentioning
confidence: 99%
“…In this part, we have clarified studies that discussed the relationship of the internal auditors with other parties. These studies have addressed the interrelation between the internal auditors and members of audit committees (Al-shaer and Zaman, 2018;Alzeban and Sawan, 2015;Davies, 2009;Quick and Henrizi, 2019;Zaman and Sarens, 2013) and the internal auditors and external auditors (Abbott et al, 2012;Argento et al, 2018;Morais and Franco 2019). It has been found that IA helps in saving audit costs in addition to enhancing and improving audit efficiency (Abbott et al, 2012).…”
Section: Internal Auditors and Other Partiesmentioning
confidence: 99%
“… Purely qualitative studies are used by more papers (9) than purely quantitative (7). The mixed approach is used by 2 papers - [6], [19].  Papers using the empirical quantitative approach are the most (7) and the mixed one -the least (2).…”
Section: Reference Approach Dimensionmentioning
confidence: 99%
“… The first model is in [13] by Frey et al The model proposes input control to be applied when public service tasks are complex. [5], [7], [9], [10], [11], [12], [14], [19], [ [14], [15], [16], [18], [19] 4 R e f e r e n c e [ 5 ] [ 7 ] 1.4Non-financial awards [13], [15], [19], [21] 5 [ 6 ] [ 8 ] 1.5Organizational culture [16], [21], [22] 6 [ 9 ] [11] 1.6Political pressure [5], [12], [14] 6 [10] [12] 1.7Promotion/ career [13], [16], [17], [19] 5 [15] [13] 1.8Reporting / whistleblowing [7], [8], [9], [16], [19], [22] 3 [20] [14] 2Professional principles [22] [16] 2.1Discipline [10], [11], [15] [8], [13],…”
Section: On the Models For 'Motivation-internal Control'mentioning
confidence: 99%
See 1 more Smart Citation
“…Argento et al (2018) examined the reliance on the work of internal auditors (IAs) by external auditors. The study shows that the professionalism and independence of IAs might be questioned.Therefore, relying on the work of IAs may affect audit quality.…”
mentioning
confidence: 99%